Preparation and biocompatibility of electrospinning PDLLA/β-TCP/collagen for peripheral nerve regeneration. Issue 66 (25th August 2017) - Lin, Fei; Wang, Xinyu; Wang, Yiyu; Yang, Yushi; Li, Yi
Abstract : A unique nerve conduit composed of poly(d, l -lactic acid) (PDLLA), β-tricalcium phosphate (β-TCP) and collagen was prepared by electrospinning for the first time. Abstract : A unique nerve conduit composed of poly(d, l -lactic acid) (PDLLA), β-tricalcium phosphate (β-TCP) and collagen was prepared by electrospinning for the first time. Scanning electron microscopy (SEM) showed that the mean diameters of the pores in the nerve conduits were less than 10 μm and greater than 1 μm. These conduits had bionic structures, larger porosity and relatively higher surface area than traditional nerve conduits, thus not only permitting the transportation of nerve growth factor and glucose but also blocking the entry of lymphatic tissue and fibroblasts. The uniform fibers of nerve conduits can mimic the natural extracellular matrix, which is beneficial to cell adhesion, cell proliferation and cell migration. PDLLA/β-TCP/collagen overcomes the challenge of low degradation rate, and maintains the basic pH environment for cell growth. PDLLA/β-TCP/collagen showed good cellular affinity and a low hemolytic rate, which is beneficial for RSC96 Schwann cells adhesion, migration and proliferation. Its good biocompatibility enables its safety in in vivo tests. A 10 mm sciatic nerve defect was bridged in vivo with PDLLA/β-TCP/collagen conduits (c) in Wistar rats. PDLLA groups (a) and PDLLA/β-TCP groups (b) were set and autotransplants (d) were used as control groups. Compared to a and b, c achieved significantly more effective regeneration of sciatic nerve injuries after 3 months' implantation and the mean diameter of soleus muscle fibers in c (39.62 ± 3.91 μm) was 1.28 times larger than that in b (30.89 ± 5.89 μm), and it was closer to that in d. The regenerated nerve fibers in c had a more regular round shape, the density of neurofilaments in c was more than those in a and b, and was close to that in d. PDLLA/β-TCP/collagen has a bionic structure, good cellular affinity and biodegradability, which can overcome the drawbacks of the current nerve conduits; hence, it holds great promise for effective of sciatic nerve regeneration.